2021
DOI: 10.1111/ocr.12554
|View full text |Cite
|
Sign up to set email alerts
|

Genetic effect of single nucleotide polymorphisms in growth hormone receptor gene on the risk of non‐syndromic mandibular prognathism in the Korean population

Abstract: Craniofacial morphology is a complex physical trait determined by genetic and environmental factors, and the relative interactions between these factors lead to varying craniofacial phenotypes. 1 From the orthodontic viewpoint, various craniofacial phenotypes refer to the relative sagittal and vertical relationships between the cranial base, maxilla and mandible. 2 Among the diverse craniofacial phenotypes, the mandibular prognathism (MP) is defined as a sagittal discrepancy on the skeletal structure in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The influence of GHR polymorphisms was investigated in several other phenotypes relating to mandibular morphology. One such study conducted by Park et al [ 21 ] and the team demonstrated the association of three polymorphisms, viz., rs6180, rs6182, and rs6184, with mandibular prognathism. Although the association was found to be insignificant, the rs6180 polymorphism was found to exhibit a marked association with that of SNMP, ANB, and SNB and effective mandibular length in females.…”
Section: Reviewmentioning
confidence: 99%
“…The influence of GHR polymorphisms was investigated in several other phenotypes relating to mandibular morphology. One such study conducted by Park et al [ 21 ] and the team demonstrated the association of three polymorphisms, viz., rs6180, rs6182, and rs6184, with mandibular prognathism. Although the association was found to be insignificant, the rs6180 polymorphism was found to exhibit a marked association with that of SNMP, ANB, and SNB and effective mandibular length in females.…”
Section: Reviewmentioning
confidence: 99%